Respuesta :
Answer:
see explanation
Step-by-step explanation:
The n th term of an arithmetic sequence is
[tex]a_{n}[/tex] = a₁ + (n - 1)d
where a₁ is the first term and d the common difference
A
There is a common difference d between consecutive terms , that is
d = 5 - 2 = 8 - 5 = 11 - 8 = 14 - 11 = 3
Thus the sequence is arithmetic with a₁ = 2 and d = 3, then
[tex]a_{n}[/tex] = 2 + 3(n - 1) = 2 + 3n - 3 = 3n - 1
[tex]a_{n}[/tex] = 3n - 1
B
There is a common difference d between consecutive terms , that is
d = 11 - 9 = 13 - 11 = 15 - 13 = 17 - 15 = 2
Thus the sequence is arithmetic with a₁ = 9 and d = 2 , then
[tex]a_{n}[/tex] = 9 + 2(n - 1) = 9 + 2n - 2 = 2n + 7
[tex]a_{n}[/tex] = 2n + 7
Answer:
so for question a the ans is 3n-1
for question b the ans is 2n+7
Step-by-step explanation:
Question A
using the formula for arithmetic progressikn(a.p) a +(n-1)d, u use this formula because it has a common differnce
a=2, where a is first term or t1
d=t2-t1=5-2=3m where d is common difference
replace the values in the formula
2+(n-1)3
2+3n-3
3n-3+2
3n-1, this is the formula for the nth term
it will be 3n -1
if u try it
3(1)-1=2
3(2)-1=5
3(3)-1=8
3(4)-1=11
3(5)-1=14
Question B
using the formula for a.p, a+(n-1)d
a=9, because it is the first term
d=t2-t1=11-9=2
replace the values in the formula
9+(n-1)2
9+2n-2
2n+9-2
2n +7,this is the formula for the7th term
if u try it
2(1)+7=9
2(2)+7=11
2(3)+7=13
2(4)+7=15
2(5)+7=17